Tahsin Reading Assistance for Islamic Boarding School Tahfidz Qur'an Muhammadiyah Daarul Arqom Sawahan Ngemplak Boyolali - Ainur Rhain; Hafidz; Husna Nashihin; Tio Hanif Srihananto; Triana Hermawati (Jurnal Pengabdian Masyarakat Bestari, 2023)
Reading Qur'an properly and correctly is obligatory for Muslims. Reading Qoran must follow what was taught by the Prophet Muhammad. People who learn Qiro'ah or reading the Qoran should not study alone without a teacher who guide them. Special knowledge is needed to improve the reading of Qoran which is called the f tajwid. The activities to improve reading or learning the Qur'an are called Tahsin. This community service research method uses the Participatory Action Research (PAR) method. The service here is trying to provide assistance to the students of the Islamic Boarding School of tahfidz Qur'an Muhammadiyah Darul Arqom Sawahan Ngemplak Boyolali. This research is field research. He hopes that in this assistance students can read the Qoran properly and correctly, in accordance with what was taught by the prophet Muhammad SAW.